Alternative solution for ex vivo lung perfusion, experimental study on donated human lungs non-accepted for transplantation - Fernandes,Lucas Matos (2015)
PURPOSE: To evaluate a new perfusate solution to be used for ex vivo lung perfusion.METHODS: Randomized experimental study using lungs from rejected brain-dead donors harvested and submitted to 1 hour of ex vivo lung perfusion (EVLP) using mainstream solution or the alternative.RESULTS: From 16 lungs blocs tested, we found no difference on weight after EVLP: Steen group (SG) = 1,097±526g; Alternative Perfusion Solution (APS) = 743±248g, p=0.163. Edema formation, assessed by Wet/dry weigh ratio, was statistically higher on the Alternative Perfusion Solution group (APS = 3.63 ± 1.26; SG = 2.06 ± 0.28; p = 0.009). No difference on PaO2 after EVLP (SG = 498±37.53mmHg; APS = 521±55.43mmHg, p=0.348, nor on histological analyses: pulmonary injury score: SG = 4.38±1.51; APS = 4.50±1.77, p=0.881; apoptotic cells count after perfusion: SG = 2.4 ± 2.0 cells/mm2; APS = 4.8 ± 6.9 cells/mm2; p = 0.361).CONCLUSION: The ex vivo lung perfusion using the alternative perfusion solution showed no functional or histological differences, except for a higher edema formation, from the EVLP using Steen Solution(r) on lungs from rejected brain-dead donors.